2018
DOI: 10.1111/jiec.12744
|View full text |Cite
|
Sign up to set email alerts
|

Backlighting the European Indium Recycling Potentials

Abstract: With increased understanding of the effects of human activities on the environment and added awareness of the increasing societal value of natural resources, researchers have begun to focus on the characterization of elemental cycles. Indium has captured significant attention due to the potential for supply shortages and nonexistent recycling at end of life. Such a combination of potentially critical features is magnified for countries that depend on imports of indium, notably many European countries. With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 52 publications
4
24
0
Order By: Relevance
“…Lastly, a retrospective on europium demand and stock accumulation and their implications on material and energy efficiency in lighting is discussed in the results. This work is part of a paper series focusing on selected metals in the EU-28 deemed relevant for interlinkages between the metal supply-demand dynamic and energy systems [33,34]. We expect that the outcomes will be informative for readers from the climate change and critical materials policy communities as well as to the lighting and electronics industries.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a retrospective on europium demand and stock accumulation and their implications on material and energy efficiency in lighting is discussed in the results. This work is part of a paper series focusing on selected metals in the EU-28 deemed relevant for interlinkages between the metal supply-demand dynamic and energy systems [33,34]. We expect that the outcomes will be informative for readers from the climate change and critical materials policy communities as well as to the lighting and electronics industries.…”
Section: Introductionmentioning
confidence: 99%
“…43 Reasons for the very low recycling rates, especially of metals and semi-metals such as indium, germanium, gallium and the REE, as are used in electronics and energy applications, are discussed elsewhere in the context of feedback control of mineral supply. 44 The specific case of indium has been addressed in another study, 45 in which the importance of end-of-life collection of the metal (which is currently almost nonexistent) to improve its recycling rate is stressed. 45 This point was also highlighted in a recent European Commission report.…”
Section: Recycling and Substitutingmentioning
confidence: 99%
“…44 The specific case of indium has been addressed in another study, 45 in which the importance of end-of-life collection of the metal (which is currently almost nonexistent) to improve its recycling rate is stressed. 45 This point was also highlighted in a recent European Commission report. 46…”
Section: Recycling and Substitutingmentioning
confidence: 99%
“…This material shows characteristics of transparency to visible light, electric conduction, and thermal reflection [13,14]. The presence of indium, with concentrations around 150 ppm, higher than that in the ores [6,[15][16][17][18], has pushed research towards the development of high-efficiency recovery processes since the metal was classified as critical raw material (CRM) by the European Commission [19,20]. Currently, China is the main global producer (around 57% of the entire amount), followed by South Korea and Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Ciacci et al, estimated an indium in-use stock of around 500 tons/year that is able to respond to the global market, which is around 15 times higher than the current European demand, proving the possibility to develop a circular indium production. The study included different kinds of waste with a metal content (e.g., motor cars, alkaline batteries), but it identified LCDs and its equipment with flat panels as potential secondary sources with the highest indium content [20]. The value of the end-of-life LCD is also confirmed by Wang et al who reported an LCD production higher than 370 million in 2014 (only in China), and they predicted that the development of an LCD recycling strategy could cover around 48% of the indium demand by 2035 [23].…”
Section: Introductionmentioning
confidence: 99%